The Paradigm of fetal surgeries: Bioethical and Biojuridical Analysis. - Oliveros Pichihua, Jennifer Claudia (2021)
In Peru since 2017, fetal surgeries have been performed to correct spina bifida and reduce the severe complications of the conceived in its intrauterine development and in its subsequent birth,  which in turn will allow a better psychobiological development; however, there is no specific regulation in this regard. In that sense, through this article, we carry out a reflection on the subject, which allows to make visible and analyze such interventions from a Bioethical and Bio-legal perspective, within the framework of protection of the dignity of the conceived, to guarantee their superior interest.